Arterial ischemic stroke in children with cardiac disease. (8th December 2015) - Asakai, Hiroko; Cardamone, Michael; Hutchinson, Darren; Stojanovski, Belinda; Galati, John C.; Cheung, Michael M.H.; Mackay, Mark T.
Abstract : Objective: To describe the spectrum of cardiac disorders, timing in relation to interventional procedures, and outcome in children with cardiac disease and arterial ischemic stroke (AIS). Methods: Children younger than 18 years with cardiac disease and radiologically confirmed AIS admitted to the Royal Children's Hospital Melbourne between 1993 and 2010 were retrospectively identified using ICD-9 and ICD-10 searches. Results: Seventy-six children with cardiac disease and radiologically confirmed AIS were identified with the median age at diagnosis of 5 months (interquartile range 0–58). Cardiac lesions included cyanotic congenital heart disease (CHD) in 42 (55%), acyanotic heart disease in 24 (29%), cardiomyopathies/myocarditis in 6 (8%), infective endocarditis in 3 (4%), and primary arrhythmias in 3 (4%). Stroke occurred following cardiac procedures in 52 patients (68%): 41 post cardiac surgery (4.6 strokes per 1, 000 surgical procedures) and 11 post cardiac catheterization (1.7 strokes per 1, 000 catheterizations). The median time from procedure to diagnosis of stroke was 3 days (interquartile range 2–7), with 68% (95% confidence interval 58%–79%) of strokes estimated to occur within the periprocedural period. Prevalence of periprocedural stroke varied by diagnostic category, but was most common in patients with cyanotic CHD undergoing palliative surgery (22/2, 256, 1%) ( p < 0.005). There were 3 AIS-related deaths, and 54 survivors (84%) had persisting neurologic deficits. Conclusions: Infants with cyanotic CHD were most frequently affected by AIS during the periprocedural period. Prospective cohort studies are required to determine effective primary and secondary prevention strategies.